Coastal management risk analysis of an embayed beach in Majorca island - Abreu, Tiago (2020)
Coastal erosion affects many coastlines around the world. This is a serious problem for the Balearic Islands, located at the western Mediterranean Sea, since the economy of the region largely relies on tourist activities along the sandy coastline. Therefore, coastal management strategies are required, particularly, in anthropized coasts as it is the case of Cala Millor beach (north-eastern Mallorca). A risk analysis for this micro-tidal sandy beach is performed in this paper. It is recognized that the beach suffers a persistent loss of sediments since its natural balance was changed due to anthropic activities that took place in that Spanish coast in the 1960s. Some solutions can be adopted to solve this problem, but it is important to be aware that, close to the shore, the seabed is covered by a native vegetation known as Posidonia Oceanica. This seagrass meadow plays an important role in this coastal system, being responsible by the lamination of the waves through energy dissipation, which are inextricably linked to coastal morphology. Therefore, any solution needs to address local specificities, and its consequent potential impact must be incorporated into the coastal risk management process. This study analyzes the failure modes identified according to the failure modes and effects analysis/failure mode, effects and criticality analysis, proposing a set of recommendations, in order to mitigate the occurrence of failure modes and to minimize risks.